An Educational Processor: A Design Approach - Raed Alqadi; Luai Malhis‎ (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In this paper, we present an educational processor developed at An-Najah National University. This processor has been designed to be a powerful supplement for computer architecture and organization courses offered at the university. The project is intended to develop an easily applicable methodology by which students get a valuable experience in designing and implementing complete processor with simple readily available off-the-shelf components. The proposed methodology is beneficial to computer engineering students enrolled at universities, especially in developing countries, where advanced laboratory equipment’s are rarely available. The design philosophy is to build a general-purpose processor using simple and wide spread integrated circuits. This methodology includes: defining an instruction set, datapath layout, ALU implementation, memory interface, controller design and implementation. For testing and evaluation purposes, a debugging tool is also built and implemented to serially connect the processor to a personal computer. In this paper, we present the methods and components used in the design and implementation phases and the tools developed to complete the design process. This methodology has shown that students enrolled in the computer architecture course get the full experience in processor design without the need for advanced laboratory equipment’s. The components used are cost efficient and methods proposed allow students to work at home, hence, this methodology has proven to be cost effective and yet very educational.